STRATEGI BAURAN PEMASARAN 9P DAN CUSTOMER CENTRISM TERHADAP PENINGKATAN JAMAAH PERSPEKTIF PEMASARAN SYARIAH (Studi: Travel Haji dan Umrah di Ajattapareng) - Umrah Yani Umar; Darmawati Darmawati; Damirah Damirah; Syahriyah Semaun; Muliati Muliati (Transpublika Publisher, 2024)
Marketing is important for business success. The right marketing strategy is very diverse, such as the 9P marketing mix and Costumer Centrism. The application of marketing strategies is important in achieving business goals. The purpose of this study is to analyze the application of sharia marketing strategies using the 9P marketing mix concept in the Hajj and Umrah travel business, and to see how this strategy can increase the number of pilgrims and customer satisfaction. This research uses the interview method to collect data. Interviews were conducted with the leaders and pilgrims of the four travel agents that became the object of research. The results showed that the 9P marketing mix increased the number of pilgrims of Hajj and Umrah travel agents in Ajattapareng. Sharia marketing principles such as transparency, honesty, and good service help increase customer satisfaction and create a competitive advantage. Data for 2019-2023 shows an increase in the number of pilgrims in 2023 thanks to packages that comply with regulations, competitive prices, satisfactory facilities, effective promotions, friendly service, and simple processes. A customer centrism approach is also applied to focus on customer satisfaction.